Implementasi Peraturan Gubernur Nomor 35 Tahun 2012 Tentang Kawasan Tanpa Rokok: Studi Kasus di Rumah Sakit Umum Haji - Putra Apriadi Siregar (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
The Medan Hajj Hospital is one of the hospitals under the North Sumatra Provincial government. The smoking-free area in the Medan Haji Hospital is a good way to prevent smoking in the hospital. This study aims to determine the implementation of Governor Regulation No. 35/2012 concerning the smoking free area in the General Hospital of Haji Medan. The existence of a smoking free area is expected to protect the community's rights to get clean air from cigarette smoke. This study uses qualitative methods using in-depth interviews and observation methods. Triangulation is carried out, namely methods, objects and sources. The instrument uses interview guidelines and observation sheets. This study indicates that there are still violations of the smoking free area policy such as cigarette butts in parking lots, canteens and mosques. Supporting facilities, such as smoking rooms, are not available, and no smoking signs are still difficult to find in some places. Human resources to carry out smoking-free area supervision are still few, supporting facilities such as no smoking room and no smoking signs are still difficult to find in several places. Medan Hajj General Hospital must improve human resources and supporting facilities such as smoking rooms and smoking prohibition signs which are still not available in several places. Sanctions must be given tougher for smokers so that smokers are deterred from smoking in smoking area areas.